2012
DOI: 10.1007/s10549-012-2106-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential anti-proliferative activities of poly(ADP-ribose) polymerase (PARP) inhibitors in triple-negative breast cancer cells

Abstract: Despite recent advances in the clinical evaluation of various poly(ADP-ribose) polymerase (PARP) inhibitors in triple-negative breast cancer (TNBC) patients, data defining potential anti-tumor mechanisms beyond PARP inhibition for these agents are lacking. To address this issue, we investigated the effects of four different PARP inhibitors (AG-014699, AZD-2281, ABT-888, and BSI-201) in three genetically distinct TNBC cell lines (MDA-MB-468, MDA-MB-231, and Cal-51). Assays of cell viability and colony formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 34 publications
4
72
1
Order By: Relevance
“…Our results are thus consistent with recent studies showing that iniparib was a weak inhibitor of PARP1. [20][21][22] Although MTT and colony formation assays are widely used to evaluate in vitro antiproliferative activities of investigational drugs, we showed that the IC 50 values obtained with the colony formation assay were consistently lower than those obtained with the MTT assays. Furthermore, no significant correlation was found between the IC 50 values obtained with the two assays across the panel cell lines investigated.…”
Section: Discussionmentioning
confidence: 64%
“…Our results are thus consistent with recent studies showing that iniparib was a weak inhibitor of PARP1. [20][21][22] Although MTT and colony formation assays are widely used to evaluate in vitro antiproliferative activities of investigational drugs, we showed that the IC 50 values obtained with the colony formation assay were consistently lower than those obtained with the MTT assays. Furthermore, no significant correlation was found between the IC 50 values obtained with the two assays across the panel cell lines investigated.…”
Section: Discussionmentioning
confidence: 64%
“…Enhanced effects of PARP inhibitors with cisplatin have been reported (Rottenberg et al, 2008;Hastak et al, 2010;Chuang et al, 2012). However, the synergistic effects in these studies are relatively weak compared with those in the reports dealing with temozolomide (Brenner et al, 2012;Kedar et al, 2012;Horton and Wilson, 2013) and camptothecin (Smith et al, 2005;Daniel et al, 2009;Zhang et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23]. PARP inhibitors are synthetically lethal in BRCA1/2-mutated tumors with DNA repair deficiencies and have been shown to be effective when combined with DNAdamaging agents in isogenic BRCA1/2-deleted cell lines and BRCA1-deficient mouse models (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%
“…This led us to hypothesize that PARP inhibition could potentially be used as a monotherapy or to enhance the therapeutic index of ionizing radiation (IR) in pHGA and DIPG. Veliparib, olaparib, and niraparib are three orally available PARP inhibitors which have all entered phase III clinical trials for adult cancer, demonstrating good tolerability in phase II studies (25)(26)(27)(28)(29)(30)(31). However, there is a lack of knowledge regarding the efficacy of these PARP inhibitors in pediatric brain tumors.…”
Section: Introductionmentioning
confidence: 99%